Attitudes of third year psychology students at the University of Limpopo (Turfloop Campus) towards the use of Marijuana - Mafumo, Masindi (My University, 2019)
A study investigating third year psychology students’ attitudes towards the use of marijuana at the University of Limpopo was undertaken. The study was quantitative in nature and used a cross sectional survey design. A random sample of 165 third year psychology students was used. The Health Belief-Model was used as a theoretical framework, which guided the study and the reporting of the research results. The self-report questions were made up of several standardised questionnaires. Quantitative data was analysed using descriptive statistics namely, frequency tables and figures as they gave a clear overall picture of the data. The Pearson correlation coefficient was used to determine if there were any significant differences between male and female participants in terms of knowledge and attitudes. The results of the study found that overall respondents had negative attitudes toward marijuana use. The study also indicated that there were no gender differences in attitudes toward marijuana use. In terms of the Pearson correlation coefficient a weak positive relationship was found between self-efficacy and attitudes toward marijuana use amongst third year psychology students. The study recommended that workshops are organised to share knowledge about marijuana and its effects.
Thesis (M.A.(Clinical Psychology)) -- University of Limpopo, 2019
Keywords: Psychology students; Marijuana; University of Limpopo; Drug abuse; Students; Marijuana